Trust in the science behind COVID-19 vaccines as a driver of vaccine acceptance in the United States, 2021–2023 - Trenton M. White; Katarzyna Wyka; Kenneth Rabin; Ayman El-Mohandes (Vaccine: X)
Objectives: To evaluate changes in public trust in the science behind COVID-19 vaccines in the United States (US) from 2021 to 2023, and to assess how loss of a family member or close friend to COVID-19, influences this trust and vaccine acceptance. Methods: Using stratified random sampling for key demographic variables, including age, gender, race/ethnicity, region, and education level, the study analyzes data from a series of cross-sectional surveys conducted in 2021, 2022 and 2023. Descriptive statistics were employed to summarize the socio-demographic characteristics of the respondents and their levels of trust in science and vaccine acceptance. Weighted logistic regression models were applied to assess the relationships between trust in science, vaccine acceptance, and socio-demographic factors. These models controlled for potential confounding variables and allowed for the estimation of adjusted odds ratios (aOR) and 95% confidence intervals (CI), highlighting the key predictors of vaccine acceptance and willingness to receive future recommended boosters. Results: The results indicate that trust in science remained relatively stable over the study period and continued to be a strong predictor of vaccine acceptance, which was higher among male respondents, those with university degrees, and those with higher than median income. Notably, the experience of personal loss was significantly related to an individual’s trust in science and vaccine acceptance. Conclusions: Trust in the science behind COVID-19 vaccines appears to have been a crucial factor in US vaccine acceptance, with respondents who expressed higher trust being significantly more likely to accept the vaccine and express willingness to take future boosters. To maintain and enhance public trust in vaccination programs, trust in health communication from public sources, particularly the CDC, must be strengthened, as trust in the CDC was also found to be significantly correlated with both vaccine acceptance and future booster uptake. Personal experiences of loss due to COVID-19 were important predictors of trust in science and vaccine acceptance, highlighting the need for public health communications to be sensitive to the emotional impact of loss and grief along with the diverse socio-economic and educational backgrounds of the US population.